Pola Komunikasi Politik Eksekutif dan Legislatif dalam Proses Pembangunan Kesejahteraan Rakyat - Zulhilmi (Asia-Pacific Journal of Public Policy, 2021)
This study aims to reveal the patterns of political communication practiced by the executive and parliament in developing communities' well-being in Aceh Tamiang Regency - Aceh Province, Indonesia. A qualitative approach was applied in collecting the data through observation, interviews, and document analysis. The finding of the study reported that the inhibiting factor for the political communication between the executive and the legislature was managing and negotiating the Regency Expenditure Budgeting. The formulation of the budgets always based on personal or political affairs - either the regent or the legislatures' businesses. Besides, the executive is always procrastinating work resulting in fatal mistakes for society. Even though the communication was intense, the most obvious misconception was the negligence of both parties in completing the budget documents that were to be submitted timely to the province. This problem is essentially the fault of the two institutions. The heedlessness they performed resulted in the loss of community welfare development funds, causing the Aceh Tamiang district to suffer losses in their physical and non-physical budgets for developing social welfare, well-being, and infrastructure development.